Effective hardware architectures for LED and PRESENT ciphers for resource-constrained applications. (20th November 2021) - Modi, Piyush; Singh, Pulkit; Acharya, Bibhudendra
Existing cyber physical systems (CPS) and internet-of-things (IoT) services depend largely on the widespread implementation of tiny smart devices for tracking, storing, monitoring, and networking applications. All IoT-enabled devices, including consumer smart devices, need secure communication mechanisms. In this paper, three different architectures are proposed based on LED and PRESENT lightweight block ciphers targeting at resource-constrained applications. This paper discusses two specific hardware architectures for the LED cipher. The first architecture introduces a round-based pipelined design in which pipeline registers are inserted in between round operations. Whereas the second is a serialised architecture that runs on a single cell per clock cycle. These proposed designs offer very efficient area-throughput tradeoff. In addition, we proposed a 32-bits datapath optimisation design to achieve high-performance, low-power, and energy-efficient hardware of PRESENT cipher encryption system. Various field programmable gate array (FPGA) platforms are used for hardware implementation and results are evaluated and compared with other related works.